RNF4 controls the extent of replication fork reversal to preserve genome stability. Issue 10 (30th May 2022) - Ding, Linli; Luo, Yi; Tian, Tian; Chen, Xu; Yang, Yulan; Bu, Min; Han, Jinhua; Yang, Bing; Yan, Haiyan; Liu, Ting; Wu, Mengjie; Zhang, Guofei; et al.
Abstract: Replication fork reversal occurs via a two-step process that entails reversal initiation and reversal extension. DNA topoisomerase IIalpha (TOP2A) facilitates extensive fork reversal, on one hand through resolving the topological stress generated by the initial reversal, on the other hand via its role in recruiting the SUMO-targeted DNA translocase PICH to stalled forks in a manner that is dependent on its SUMOylation by the SUMO E3 ligase ZATT. However, how TOP2A activities at stalled forks are precisely regulated remains poorly understood. Here we show that, upon replication stress, the SUMO-targeted ubiquitin E3 ligase RNF4 accumulates at stalled forks and targets SUMOylated TOP2A for ubiquitination and degradation. Downregulation of RNF4 resulted in aberrant activation of the ZATT–TOP2A–PICH complex at stalled forks, which in turn led to excessive reversal and elevated frequencies of fork collapse. These results uncover a previously unidentified regulatory mechanism that regulates TOP2A activities at stalled forks and thus the extent of fork reversal.